The correlation between cervical proprioception and cranio-cervical flexion tests in patients with whiplash-associated disorders - Snyckers, Merle (My University, 2008)
ABSTRACT: Whiplash-associated disorders are a common occurrence. Physiotherapy rehabilitation of such disorders include, among others, improving the recruitment ability of the deep cervical flexor muscles. Cervical proprioception, which has recently gained attention, is not commonly addressed. Evidence points to a possible link between cervical proprioception and deep cervical flexor recruitment ability. This study aimed to determine whether such a correlation exists. This is significant as it highlights the role that recruitment training of the deep cervical flexors has on cervical proprioception. A correlation study design was employed that involved 29 patients with whiplashassociated disorders. They were tested in their ability to perform the cranio-cervical flexion test and Revel’s test for proprioception. Linear regression was employed to interpret the results. This study concluded that a correlation exists between the ability to perform the craniocervical- flexion test and cervical proprioception.
Keywords: cervical proprioception; whiplash; deep cervical flexors